Nuclear Beta Decay: Relativistic Theory and Ab Initio Simulations of Electroweak Decay Spectra in Medium‐Heavy Nuclei and of Atomic and Molecular Electronic Structure (Adv. Theory Simul. 11/2018). Issue 11 (6th November 2018) - Morresi, Tommaso; Taioli, Simone; Simonucci, Stefano
Abstract : In article number1800086, Simone Taioli and co‐workers develop a new theoretical and computational method for calculating beta‐decay and electron‐capture spectra of medium to heavy mass nuclei. This approach deals with relativistic and many‐body effects within the electron shells and can be easily extended to include nuclear structure details along the nuclide chart and to calculate the electronic structure of polycentric systems.